2022
DOI: 10.1097/pas.0000000000001846
|View full text |Cite
|
Sign up to set email alerts
|

NF2-mutated Renal Carcinomas Have Common Morphologic Features Which Overlap With Biphasic Hyalinizing Psammomatous Renal Cell Carcinoma

Abstract: Genetic alterations involving NF2 occur at low frequencies in renal cell carcinoma across all of the major histologic subtypes and have been associated with adverse outcomes. To better characterize tumors harboring these alterations, we identified 14 cases with NF2 mutations that had been previously diagnosed as papillary renal cell carcinoma; renal cell carcinoma, unclassified; or translocation associated renal cell carcinoma. These tumors were characterized by a tubulopapillary architecture, sclerotic stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Tumours within the spectrum of RCC purportedly driven by NF2 inactivation described in prior studies (henceforth referred to as 'BHP RCC') [7][8][9][10] were retrieved from the personal files of the authors, including tumours previously reported by Argani et al, 7 Paintal et al, 8 and Gopinath et al, 10 as well as newly identified tumours. Additionally, pathology databases and personal consultation files were queried for tumours diagnosed as papillary RCC, TFE3-rearranged RCC, TFEB-altered RCC (TFEB-rearranged RCC and TFEB-amplified RCC), and MTSCC (NF2 mutation status unknown) with archival formalin-fixed paraffinembedded (FFPE) tissue available for IHC.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tumours within the spectrum of RCC purportedly driven by NF2 inactivation described in prior studies (henceforth referred to as 'BHP RCC') [7][8][9][10] were retrieved from the personal files of the authors, including tumours previously reported by Argani et al, 7 Paintal et al, 8 and Gopinath et al, 10 as well as newly identified tumours. Additionally, pathology databases and personal consultation files were queried for tumours diagnosed as papillary RCC, TFE3-rearranged RCC, TFEB-altered RCC (TFEB-rearranged RCC and TFEB-amplified RCC), and MTSCC (NF2 mutation status unknown) with archival formalin-fixed paraffinembedded (FFPE) tissue available for IHC.…”
Section: Methodsmentioning
confidence: 99%
“…Testing for NF2 was assessed using the solid tumour panels by the University of Chicago, Memorial Sloan Kettering Cancer Center, UT Southwestern, University of Florida Health Jacksonville Molecular Pathology Laboratory, and Nanjing Geneseeq Technology (Nanjing, China) as described in the corresponding publications. [7][8][9][10] Results…”
Section: M M U N O H I S T O C H E M I S T R Ymentioning
confidence: 99%
See 3 more Smart Citations